2010
DOI: 10.2109/jcersj2.118.530
|View full text |Cite
|
Sign up to set email alerts
|

Effects of titanium surface treatment on adhesive properties of hydroxyapatite ceramics coating to titanium substrates by double layered capsule hydrothermal hot-pressing

Abstract: This report described the effects of Ti surface modification with NaOH hydrothermal solution on adhesion strength of HA coating produced by newly developed hydrothermal (DC-HHP) method. 2 kinds of surface layer (containing anatase-type TiO 2 or not) were formed on Ti surface by immersing to 5 mol/L NaOH solution before HA coating process. Pull out tests were conducted to obtain an estimate for the adhesion properties of the HA coating. Shear strength of specimens with 5 mol/L NaOH treated at 423 K for 2 hours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Between inner and outer capsule, alumina powder is placed to maintain the space for water retreat. Hydroxyapatite-coated magnesium [129], and titanium [133,134,189], were produced by using DC-HHP.…”
Section: Hydrothermal Hot Pressingmentioning
confidence: 99%
“…Between inner and outer capsule, alumina powder is placed to maintain the space for water retreat. Hydroxyapatite-coated magnesium [129], and titanium [133,134,189], were produced by using DC-HHP.…”
Section: Hydrothermal Hot Pressingmentioning
confidence: 99%
“…Just a few publications were found on the topic and they were devoted to HA deposition on AZ31 Mg alloy [562] and Ti [9,563,564]. In order to create suitable hydrothermal conditions, double-layered capsules were used: the inner capsule encapsulated the deposited materials and a substrate, while the outer one was subjected to isostatic pressing under the hydrothermal conditions.…”
Section: A Double Layered Capsule Hydrothermal Hot Pressingmentioning
confidence: 99%
“…These results also revealed that a crack propagation occurred within the HA deposits but not along the HA/Ti interface. Therefore, the fracture property of the HA/Ti interface was higher than that of the HA bioceramics only[9,563,564].4.4.3. Detonation gun sprayingDetonation gun spraying is both a high temperature and a high velocity technique, which introduced a higher degree of melting to starting powder.…”
mentioning
confidence: 92%
“…There are only a few publications on the subject and they are devoted to HA deposition on AZ31 Mg alloys [620] and Ti [9,621,622]. A double-layer capsule was used to create suitable hydrothermal conditions: the inner capsule encapsulated the deposited material and substrate, while the outer capsule was subjected to hydrostatic pressing under hydrothermal conditions.…”
Section: A Double Layered Capsule Hydrothermal Hot Pressingmentioning
confidence: 99%